RANDOMIZED ANTICANCER AND CYTOTOXICITY ACTIVITIES OF GUIBOURTIA COLEOSPERMA AND DIOSPYROS CHAMAETHAMNUS. - Dushimemaria, Florence; Preez, C. Iwanette Du; Mumbengegwi, Davis R. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Plants have consistently proven to be a reliable and yet not fully explored source of medicines. In light of this, there is a constant demand for new treatment regimens for cancer. Namibia has a rich diversity of plant species of over 4300 with 17 % of them being endemic to Namibia. Plants growing in Namibia’s diverse climatic zones produce many secondary metabolites as part of adaptation to their environment. This article focused on the screening of such phytochemicals and their cytotoxic and anticancer properties in vitro. Two Namibian plants Diospyros chamaethamnus and Guibourtia coleosperma were randomly selected for this purpose. Materials and Methods: The plants were screened for the presence of coumarins, alkaloids, flavonoids, anthraquinones, steroids and terpenoids using thin layer chromatography. Anticancer screening was performed on a panel of three cancer cell lines, while cytotoxicity was determined using a human fibroblast cell line, both using the SRB method. Results: Alkaloids, anthraquinones, flavonoids and steroids were detected in both organic and aqueous extracts of the two plants. The organic plant extracts had a greater anti-proliferative effect on the cancer cell lines than the aqueous extracts; the D. chamaethamnus organic root extract was the most potent with an IC50 of 16.08, 29.12 and 24.67 μg/mL against TK10, UACC62 and MCF7 cells, respectively. Furthermore, cytotoxicity analysis revealed the non-toxic nature of the extracts, except for the organic root extract of D. chamaethamnus that showed significant cytotoxicity (IC50 13.03 μg/mL). Conclusion: D. chamaethamnus is a potential candidate for the development of a plant based cancer treatment. The study showed the value of random screening in drug discovery from plants for pharmacological activity that is unrelated to their ethnomedicinal uses.